Pengaruh Penerapan Kurikulum 13 Pada Mata Pelajaran Pendidikan Agama Islam Terhadap Perilaku Sehari-Hari Dan Kualitas Bacaan Al-Qur’an Siswa di SMA IT Astri Al-Ikhlas Desa Tanjung Batu Seberang - Yuniza Mulditasari; Lisa Fitriani; Asila Wati; Ki Agus Ihsan Nulkhoir; Dwi Noviani (Student Research Journal, 2024)
This research aims to describe the effect of implementing curriculum 13 in Islamic religious education subjects on students' daily behavior and the quality of students' Al-Qur'an reading at SMA IT Astri Al-Ikhlas, Tanjung Batu Seberang Village. The Islamic religious education curriculum in public schools needs to be developed so that it is able to balance and respond to the challenges of the times. This research was conducted using interviews and bibliography studies. The results of this research found that the implementation of the Islamic religious education curriculum at SMA IT Astri Al-Ikhlas integrates three educational environments (school, family and community), as well as science with Islamic teachings. The curriculum used is the 2013 curriculum based on the teachings of Manhaj Tarbiyah as reflected in the curriculum components which use an exemplary approach.